SISTEM INFORMASI AKADEMIK PADA PONDOK PESANTREN LITAHFIDZIL QUR’AN KABUPATEN BATANGHARI BERBASIS WEB: New Student Registration, Web, CodeIgniter, phpMyAdmin. - -, Nilawati (JURNAL AKADEMIKA, 2017)
Thesis Writing entitled Academic Information System At Arrahman Litahfidzil Pondok Pesantren Qur'an Batanghari. This information system application is designed to convey information and making reports of students enrolled to the general public, especially to prospective students through this application. In addition, for applicants can view academic information easily and efficiently. The method used in the writing of this thesis is Observation, Library Studies, and Interview. The program was developed using the CodeIgniter Programming Language as the interface. And discuss the ways of making data processing applications that consist of input, process and output using the facilities contained on the Web, and phpMyAdmin as the database. With the application of Academic Information System At Pondok Pesantren Arrahman Litahfidzil Qur'an is the acceptance of new students who process data, usually done manually and complicated with the transfer of data repetitive and unstructured and time consuming can now be done more easily, quickly and can Reduce errors in the process of storing registration data and facilitate the making of reports quickly and accurately.